Solve for x. x – 2(2 – 3/2 x) = 2(4 – x) + 1

Question

Solve for x. x – 2(2 – 3/2 x) = 2(4 – x) + 1

in progress 0
Ivy 5 days 2021-10-08T06:56:17+00:00 1 Answer 0

Answers ( )

    0
    2021-10-08T06:57:35+00:00

    Answer:

    x = 13/6

    Step-by-step explanation:

    We are the following expression;

           x – 2(2 – (3/2)*x) = 2(4 – x) + 1

           x – (4 – 3*x) = 8 – 2*x + 1

           x – 4 + 3*x = 8 – 2*x + 1

             4*x + 2*x = 9 + 4

                 6*x = 13

                  x = 13/6

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )